Nutrient Status of Vermicompost of Urban Green Waste Processed by Three Earthworm Species—Eisenia fetida, Eudrilus eugeniae, and Perionyx excavatus - Swati Pattnaik; M. Vikram Reddy (Applied and Environmental Soil Science)
Major nutrient status of vermicompost of vegetable market waste (MW) and floral waste (FW) processed by three species of earthworms namely, Eudrilus eugeniae, Eisenia fetida, and Perionyx excavatus and its simple compost were assessed across different periods in relation to their respective initiative substrates. Their physical parameters—temperature, moisture, pH, and electrical conductivity—were also recorded. The nutrients—nitrogen, phosphorus, potassium, calcium, and magnesium—increased in the vermicompost and compost while the organic carbon, C/N and C/P ratios decreased as the composting process progressed from 0 to 15, 30, 45, and 60 days. The nutrient statuses of vermicomposts of all earthworm species produced from both the wastes were more than that of the compost and that of their respective substrates. Moreover, the vermicompost produced by E. eugeniae possessed higher nutrient contents than that of E. fetida, P. excavatus, and compost. The MW showed higher nutrient contents than the FW. Thus, vermicomposting is the paramount approach of nutrient recovery of urban green waste.